Protocols Of Cipher Suite - Yesiltepe, Mirsat; Kose, Gulsah; Karadeniz, Sinem (IEEE, 2016)
The value of software is proportional to the value of quality. Quality is one of the elements of security. There are two basic concepts that basically contains the security elements it contains. When tested in terms of security software are basically just white-box testing can be used to test the internal structure and may only be used in the user's black box testing. This concept is the concept of testing basic concepts contains many sub-types. This concept is also one of the sub-encryption package, gives an idea of the overall structure of the system's security over the information it contains. In this study, the protocols contained in encryption package was addressed to the differences in the protocols.
Keywords: Computer Science; Engineering